PENDAMPINGAN PENGGUNAAN GOOGLE COLAB PADA PEMBELAJARAN PYTHON DAN MACHINE LEARNING BAGI DOSEN MATEMATIKA DI PALEMBANG - Octarina, Sisca; Puspita, Fitri Maya; Yuliza, Evi; Indrawati, Indrawati (Jurnal Pepadu, 2025)
Learning and research in higher education have experienced many challenges and problems, especially after the Covid-19 pandemic. However, these challenges have been overcome using online learning platforms such as Moodle University, Zoom, Google Meetings, and Microsoft Teams. However, this has not been fully resolved in the field of research. It is sometimes complicated for research teams to work together on research. Research records or research logbooks are not quickly sent via email. In addition, research records, such as computer programming, require direct handling of the program that has been created without copying and pasting. Mathematics research also requires fast and dynamic access. Google Colab is a Google collaboration that provides free, cloud-based tools for education and research. Google Colab is particularly eye-catching because it gives users free access to GPU services as a computing backend that can be used for 12 hours. If you want to learn Python and machine learning, buying a computer with an additional GPU is unnecessary. The training process in these two fields is tricky, especially if the equipment is inadequate. Mathematics lecturers in Palembang need assistance because lecturers' knowledge about Google Colab is still very low. The implementation team conducted a mentoring activity on using Google Colab for machine learning and Python through the Zoom platform. The activity consists of several stages: explanation, tutorial, and practice.